A trial design to maximize knowledge of the effects of rodatristat ethyl in the treatment of pulmonary arterial hypertension (ELEVATE 2). (11th May 2022) - Lazarus, Howard M.; Denning, Jill; Wring, Stephen; Palacios, Michelle; Hoffman, Sidra; Crizer, Katelyn; Kamau‐Kelley, Watiri; Symonds, William; Feldman, Jeremy
Abstract: Serotonin plays a key role in the development and maintenance of the pathobiology associated with pulmonary arterial hypertension (PAH). Platelet‐driven and locally produced serotonin from lung tissue and arterial endothelial cells induce excessive growth of pulmonary artery smooth muscle cells. The unchecked growth of these cells is a major driver of PAH including the remodeling of pulmonary arteries that dramatically reduces the diameter and flexibility of the arterial lumen. Tryptophan hydroxylase 1 (TPH1) is the rate‐limiting enzyme for biosynthesis of serotonin and is upregulated in PAH arterial endothelial cells, supporting TPH1 inhibition to treat PAH. Targeting the serotonin pathway via inhibition of peripheral serotonin and local production in diseased tissues, rather than individual receptor‐mediated or receptor‐independent mechanisms, may result in the ability to halt or reverse pulmonary vascular remodeling. Rodatristat ethyl, a prodrug for rodatristat, a potent, peripheral inhibitor of TPH1, has demonstrated efficacy in monocrotaline and SUGEN hypoxia nonclinical models of PAH and robust dose‐dependent reductions of 5‐hydroxyindoleacetic acid, the major metabolite of serotonin in plasma and urine of healthy human subjects. ELEVATE 2 (NCT04712669) is a Phase 2b, double‐blind, multicenter trial where patients with PAH are randomized to placebo, 300 or 600 mg twice daily of rodatristat ethyl. The trial incorporates endpoints to generate essential clinical efficacy, safety, pharmacokinetic, and pharmacodynamic data needed to evaluate the ability of rodatristat ethyl to ameliorate PAH by halting or reversing pulmonary vascular remodeling through its unique mechanism of TPH1 inhibition. Herein we describe the experimental design highlighting the trial's unique features.